RECONSTRUCTING THE SECOND-WAVE FEMINISM: APPROACHES BETWEEN NANCY FRASER AND AXEL HONNETH. - Ribeiro, Douglas Carvalho (2015)
This article aims to analyze the proximity between the theories of Axel Honneth and Nancy Fraser, considering not only the famous discussion redistribution versus recognition. The main focus will lie on Nancy Frasers "Feminism, Capitalism and the cunning of history", where the author asserts its claim to approach the deepest foundations of Honneths thought in order to rebuild the claims of so-called second-wave feminism. At first, the bases of Honneth s thought will be investigated - which ultimately are the bases of the critical tradition. Subsequently, from the analysis of the concepts "blockade" and "reconstruction", the main features of the second generation feminism will be examined, well as the causes of its failure and the prospects for a post-neoliberal feminist theory.